2021
DOI: 10.1002/srin.202100235
|View full text |Cite
|
Sign up to set email alerts
|

Study on the High‐Temperature Evolution and Formation Mechanism of Inclusions in Te‐Treated Resulfurized Special Steel

Abstract: Te can effectively modify MnS inclusion to improve the anisotropy and machinability of steel. To figure out the mechanism of high‐temperature evolution and formation of inclusions, a high‐temperature confocal laser scanning microscope is used to in situ observe the performance of inclusions. In the steel with 22 ppm Te, Te mainly dissolves in MnS; no MnTe is generated. During the heating process, MnS inclusion remains solid state and no obvious phase change can be observed. In comparison, MnS–MnTe binary inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…[26] Copyright 2016, Elsevier. [57] Copyright 2021, John Wiley and Sons. Combined with the MnTe-MnS binary phase diagram, the precipitation rules of the MnTe-MnS composite inclusions at low and high Te contents were inferred by Shen et al, [23,57] and the schematic diagram is shown in Figure 7.…”
Section: Precipitation Mechanism Of Telluride In Steelmentioning
confidence: 99%
See 3 more Smart Citations
“…[26] Copyright 2016, Elsevier. [57] Copyright 2021, John Wiley and Sons. Combined with the MnTe-MnS binary phase diagram, the precipitation rules of the MnTe-MnS composite inclusions at low and high Te contents were inferred by Shen et al, [23,57] and the schematic diagram is shown in Figure 7.…”
Section: Precipitation Mechanism Of Telluride In Steelmentioning
confidence: 99%
“…[57] Copyright 2021, John Wiley and Sons. Combined with the MnTe-MnS binary phase diagram, the precipitation rules of the MnTe-MnS composite inclusions at low and high Te contents were inferred by Shen et al, [23,57] and the schematic diagram is shown in Figure 7. When the Te content is low, in the liquid-phase solution formed by Mn, S, and Te, MnS preferentially precipitates and aggregates to form a large-sized MnS core.…”
Section: Precipitation Mechanism Of Telluride In Steelmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3] Manganese sulfide (MnS) is a typical nonmetallic inclusion that can effectively improve the machinability of the sulfur-containing steel. [4,5] However, it can exert adverse effect on the performance of steel if the precipitation of MnS is controlled improperly. The coarse and aggregated MnS precipitates deform easily in the rolling process and lead to anisotropy and deterioration in mechanical properties of the steel.…”
Section: Introductionmentioning
confidence: 99%